Urinary metabolic evaluation of stone formers-a Malaysian perspective - Hong, Y.H.; Dublin, N.; Razack, A.H.; Mohd, M.A.; Husain, R. (2012)
OBJECTIVE To investigate the urinary metabolic excretion pattern among local stone formers given the great differences in the intrinsic and extrinsic risk factors as well as the urinary metabolic excretions compared with other populations. METHODS Thirty urinary stone formers out of an initial 62 recruited provided a complete 24-hour urine sample for metabolic evaluation. Student's t-test and Pearson correlation test were used for the statistical analysis. RESULTS Urinary volume (1719 +/- 712 vs 1215 +/- 575, P < .05) and oxalate excretion (0.386 +/- 0.111 vs 0.306 +/- 0.104, P < .05) were significantly higher among stone formers than controls. Other commonly studied urinary parameters and urinary melamine did not differ significantly between the 2 groups. Similarly, the calcium/citrate ratio was unable to discriminate the stone formers from their controls. Hypocitraturia was the most prevalent urinary abnormality found in stone formers and low urinary citrate excretion was a general phenomenon in both stone formers and controls. Comparing within the stone formers cohort, the recurrent stone formers had a significantly higher urinary saturation and calcium excretion than their first-time stone former counterparts. CONCLUSION Elevated urinary oxalate level was the most important urinary risk factor among the local stone formers. A low urinary citrate excretion appeared to be a general phenomenon among the studied cohorts. UROLOGY 80: 529-534, 2012. (c) 2012 Elsevier Inc.